2019
DOI: 10.1093/brain/awz211
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian inference and hallucinations in schizophrenia

Abstract: This scientific commentary refers to ‘Acquisition of visual priors and induced hallucinations in chronic schizophrenia’, by Valton et al. (doi:10.1093/brain/awz171).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Computational methods in schizophrenia have mostly been generative models based on the Bayesian predictive coding framework—for example, the hierarchical Gaussian filtering approach (Powers et al ., 2017 ; Henco et al ., 2020 ; Charlton et al ., 2022 ; Sheffield et al ., 2022 ), reinforcement learning (Pratt et al ., 2021 ; Geana et al ., 2022 ), and the active inference Markov decision process model that attempts to dissect unobservable mechanistic variables based on actions taken by an agent to promote desired outcomes (Friston et al ., 2016 ). All of these approaches use a single-person task design and mainly target hallucinatory and delusional positive symptoms, reward-related decision-making, and thought and language deficits in PSZ (Siemerkus et al ., 2019 ; Deserno et al ., 2020 ; Smith et al ., 2021 ; Charlton et al ., 2022 ; Knolle et al ., 2022 ; Limongi et al ., 2022 ). A recent study examining guilt-related interpersonal dysfunction in obsessive-compulsive personality disorder using social interaction tasks applied two computational models (guilt aversion and Fehr–Schmidt inequity aversion models), and demonstrated that interpersonal dysfunction was the result of maladjustment to and poor compliance with social norms (Xiao et al ., 2022 ).…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Computational methods in schizophrenia have mostly been generative models based on the Bayesian predictive coding framework—for example, the hierarchical Gaussian filtering approach (Powers et al ., 2017 ; Henco et al ., 2020 ; Charlton et al ., 2022 ; Sheffield et al ., 2022 ), reinforcement learning (Pratt et al ., 2021 ; Geana et al ., 2022 ), and the active inference Markov decision process model that attempts to dissect unobservable mechanistic variables based on actions taken by an agent to promote desired outcomes (Friston et al ., 2016 ). All of these approaches use a single-person task design and mainly target hallucinatory and delusional positive symptoms, reward-related decision-making, and thought and language deficits in PSZ (Siemerkus et al ., 2019 ; Deserno et al ., 2020 ; Smith et al ., 2021 ; Charlton et al ., 2022 ; Knolle et al ., 2022 ; Limongi et al ., 2022 ). A recent study examining guilt-related interpersonal dysfunction in obsessive-compulsive personality disorder using social interaction tasks applied two computational models (guilt aversion and Fehr–Schmidt inequity aversion models), and demonstrated that interpersonal dysfunction was the result of maladjustment to and poor compliance with social norms (Xiao et al ., 2022 ).…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…This explanation for perception and action has led quite naturally to descriptions of hallucinations as perceptual inference based on overly precise priors. [19][20][21] This theory supposes that prior beliefs in perceptual stimuli are so strong that resulting inferences are resistant to the empirical absence of such stimuli. In contrast, delusions are the result of imprecise prior beliefs such that sensory attenuation fails and sensations inappropriately alter priors 22 phenomenologically this results in the attribution of meaning to events that should be trivial.…”
Section: Prediction Errors Entropy and Free-energy Minimisationmentioning
confidence: 99%
“…In recent years, predictive processing models have arguably become the dominant approach to explain hallucinations in SSD. There are many subtypes of predictive processing models that include self-monitoring approaches ( Farrer and Franck, 2007 ; Ford and Hoffman, 2013 ) and Bayesian approaches ( Friston, 2005 ; Siemerkus et al, 2019 ). Both approaches maintain that a critical function of our brains is to make accurate predictions; to do this, our brains are on a quest to minimize prediction errors (e.g., mismatches between outcomes we anticipate vs. outcomes we actually perceive).…”
Section: Introductionmentioning
confidence: 99%
“…Self-monitoring theories emphasize the predictions that we make about the sensory consequences of our motor actions (including speech), and refer to this predictive signal as a corollary discharge ( Ford et al, 2001 ; Ford and Mathalon, 2005 , 2019 ). Meanwhile, Bayesian approaches offer a more general framework for thinking about how our prior beliefs about what will happen next (referred to as “priors”) guide our inferences in noisy or ambiguous environments ( Friston, 2005 ; Siemerkus et al, 2019 ). A central idea in Bayesian models of perception is that the initial prior is integrated and compared with new perceptual information conveyed by the sensory organs to produce the final percept (referred to as a “posterior”) ( Friston, 2005 ; Siemerkus et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation